The Government Liability for Environmental Damage Caused by Mining - Fadlulloh, Muhammad Dito; Wardana, Dodi Jaya (Law Development Journal, 2024)
Indonesia is rich in natural resources that can be utilized for development purposes and generate profits. One of the natural resources that can provide benefits is the mining sector. However, ironically, in addition to generating profits, mining businesses can also cause losses in the form of damage/pollution to the environment around the mine. This type of research is normative research that includes various approaches, research specifications, data collection methods, and data analysis techniques. In this study, a normative approach was used with the aim of analyzing various legal regulations related to mining cases in Indonesia, both those applicable nationally and regionally. The results of the study indicate that mining activities can damage the surrounding environment and deplete natural resources. Conflicts of interest between mining companies, the government, and indigenous peoples are another factor causing social unrest. As a result, adequate government regulations are needed to control mining activities, including operating permit requirements, environmental responsibility, and supervision. To ensure that the community can benefit from mining activities, the government must also focus on regional economic development and education initiatives.